Association of frailty with nutritional parameters in patients with chronic kidney disease - Evcen, Recep; Koçak, Mehmet Zahid; Elsürer Afşar, Rengin (The European Research Journal, 2024)
Objectives: Frailty is a significant clinical syndrome characterized by greater susceptibility to stressors due to the dysfunction of multiple organ systems, which increases in prevalence with age. This study was performed to investigate relations between frailty and nutritional parameters in patients with chronic kidney disease (CKD). Methods: This cross-sectional study involved 100 CKD patients aged 50 years or older. Frailty was assessed using the Edmonton Frailty Scale (EFS) and Fried’s Frailty Scale (FFS). The patients nutritional status was assessed using the Mini Nutritional Assessment (MNA) and the routine laboratory tests. Results: The study included 100 patients, consisting of 41 females and 59 males. The mean age of the participants was 65.3±9.3 years. The median glomerular filtration rate (GFR) of the patients was 23 mL/min/1.73 m2) (min: 3-max: 65). According to the MNA, 15 patients had normal nutritional status, 63 were at risk of malnutrition, and 22 were malnourished. According to the EFS score, four patients were categorized as not frail, 11 as vulnerable, 25 with mild frailty, 21 with moderate frailty, and 39 with severe frailty. According to the FFS score, six patients were non-frail, 30 were classified as pre-frail, and 64 were considered frail. Conclusions: Frailty and malnutrition in patients with CKD were independently related to all other factors examined in this study. Screening for malnutrition at the early stages in patients with CKD and the appropriate treatment may prevent the development of frailty.